The Meaning of Place in Historic Building (Case Study: Three Urban Heritage Tourism Destinations at Kesawan Medan) - Permana, Sendi; Lubis, Darwin Parlaungan; Sugiharto; Marbun, Sahala Fransiskus; Amelia, Pidia (Jurnal Penelitian Geografi, 2025)
Based on the Regional Spatial Planning of Medan City for the years 2011-2031, several Cultural Heritage Areas have been established that include various historical buildings, one of which is located in the Old City area of Kesawan. The presence of historical buildings such as the Lonsum Building, Tjong A Fie, and Pos Bloc coexists with the rapid business and culinary activities on Ahmad Yani Street and Balai Kota Street. There are indications that a shift in visitation orientation has occurred where the meaning of tourism is stronger compared to a comprehensive exploration of history. The aim of this research is to analyze the meaning of place at three historical buildings and its implications for regional development. This research is qualitative with a geographical approach. In-depth interviews were conducted with 36 informants selected through purposive sampling. The research results show that the meaning of place in the three historical buildings is more dominated functionally, socially, and emotionally than by regional romanticism. The shift in the meaning of historical buildings is a consequence of the massive development of alternative tourism in urban areas. Therefore, it is necessary to reorganize the cultural heritage area involving elements of the community, government, and private sector, with the hope that the authentic value of historical buildings is not entirely eroded by the modernity of urban development.